“Join the Union or you’ll Die”: Songs Relating to the Labour Union Movement in Canada’s Coal Mining Communities - O'Donnell, John (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1992)
This article reflects some of the results of my research into the songs of Canada’s coal mining communities. In particular, it is a study of songs which emerged as a result of the Labour Union Movement on this continent. The hardships and sacrifices endured by Canadian coal miners, beginning with the earliest attempts to unionize in 1879 through the great strikes of the early twentieth century, have been well-documented in song. Although not all the songs are traditional in the sense of having been transmitted orally from generation to generation, they do offer a valuable insight into the traditions which nurtured the growth of unionism in this country.